Study of association of thrombocytopenia and serological parameters in dengue fever with special reference to NS1 antigen in hilly Region of Northern India - Nidhi Negi,; Yogita Rawat,; Shekhar Pal,; Ruhi Hasan,; Arti Negi, (Asian Journal of Medical Sciences, 2024)
Background: Dengue fever is an arthropod-borne disease transmitted to humans by Aedes aegypti mosquitoes and one of the leading causes of arthropod-borne viral disease in the world. Aims and Objectives: The present study aims to analyze any association between platelet count and immunochromatography -based dengue serology tests. Materials and Methods: This was a cross-sectional study conducted in Government Doon Medical College and Hospital. A total of 19,208 clinically suspected cases of dengue who reported in various outpatient departments, emergency services, and inpatient departments of our hospital between June 2023 and November 2023 were included in this study. Samples were tested by rapid immunochromatographic test for dengue non-structural protein 1 (NS1) antigen, immunoglobulin M (IgM), IgG, and platelet count was also obtained and a comparison was made. Results: Out of total 19,208 samples tested, 4876 (25.38%) samples were positive for NS1, 589 (3.06%) samples were positive for IgM. Majority of the patients were in the age group of 21–40 years 9274 (48.28%). 11,753 (61.19%) were males and 7455 (38.80%) were females. A strong correlation was seen between NS1 and thrombocytopenia where a total of 2737/4876 (n=56.13%) patients showed positivity in NS1 with low platelet counts. Conclusion: Detection of NS1 antigen helps in early diagnosis of dengue to avoid complications significantly. In confirmed dengue cases with fever, thrombocytopenia is more consistently found and can be used as a predictor to reduce the morbidity and mortality of dengue disease.